Review of Verdade e política na obra de Hannah Arendt de Pereira, Curitiba, Appris editora, 2019. - Bollatti, Luciano Matias (Pescadora de Perlas. Revista de estudios arendtianos, 2023)
If we base ourselves on Arendt's reading of the dispute between philosophy and politics in Plato, truth and politics would seem to be two irreconcilable concepts for her theory of action. However, if we venture, as Geraldo Pereira did here, to investigate and make a finer analysis of Arendt's work in dialogue with interpreters of the author, a thesis as powerful for Arendt's thought as it is enlightening for certain current dangers can be founded. While philosophical truth closes the possibility of opinions in the common world, another kind of truth is capable of rescuing reality at times when ideology and organized lies isolate us from the common world: telling the truth of the facts.